Nutritional assessment of the area of influence of the marginal road Geography, economy, health, dietary intake, clinic and anthropometric - Guzmán Barrón, Alberto (1969)
This time, we present the work done in the city of Tarapoto, influential in the development of eastern Peru and where the work of the "Marginal Road" linking north and south are a number of centralized populated places and then the access roads to the mountains and coast, ensure a means of communication that allow them out of isolation in which they live and the development of agro-livestock activities in the extensive area of high forest. in this way you can have land to house hundreds of thousands of peasants living in subhuman conditions in the mountains and overpopulated coast.